ON THE [ArIV]/[ArIII] LINE RATIO IN PLANETARY NEBULAE - Carlos Reyes, R. E. (2000)
Previous spectroscopic studies of planetary nebulae have shown that the observed [ArIV]/[ArIII] line ratio is not reproduced by photoionization models. We show that this discrepancy disappears if we consider an adequate combination of the filling factor and radial density profile.